The Relationship between Endogenous Factors and Contact Dermatitis on Electroplating Workers in Durungbanjar - Yasmien Alvira; Danang Setia Budi (The Indonesian Journal of Occupational Safety and Health, 2020)
Introduction: Occupational contact dermatitis can be interpreted as a health problem on the skin caused by exogenous and endogenous factors related to work. Electroplating is one of high-risk jobs that caused occupational contact dermatitis because of direct contact with chemicals during working. In addition, contact dermatitis is also affected by individual factors of each worker. This research purpose was to identify the relationship among endogenous factors and the occupational contact dermatitis case in metal coating workers in home industry. Method: The research design used was observational with a cross sectional approach. The total population was used as the sampling technique in this study with a total of 28 workers from two metal coating industries in Durungbanjar Village consisting 13 workers from CV. M and 15 workers from CV. N. The data were obtained from the survey, sighting, and medical record notes. Variables from the study included age, working period, history of illness, and personal hygiene. The data were processed using the coefficient contingency test. Result: There were 64.3% of electroplating workers experienced contact dermatitis. The age aspect has a weak relationship (c = 0.295), the working period element has a weak relationship (c = 0.298), the disease history factor has a weak relationship (c = 0.352) and the individual hygiene factor has a strong relationship (c = 0.547). Conclusion: The endogenous factors including age, working period, history of disease, and personal hygiene affect contact dermatitis case. There is a strong relationship between personal hygiene and contact dermatitis cases in metal coating workers. The worse personal hygiene of the workers, the higher risk of workers experiencing contact dermatitis. Age, working period, and history of disease had weak relationship with contact dermatitis case.Keywords: contact dermatitis, endogenous factors, metal coatings